2013
DOI: 10.3109/0886022x.2013.773835
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers of Acute Kidney Injury in the General Adult ICU: A Review

Abstract: Acute kidney injury is one of the most frequent problems occurring in the critically ill patients of the intensive care units and it is well established that it increases both morbidity and mortality in these patients. Moreover, despite technological and pharmaceutical advances during the last decades, the incidence as well as the mortality associated with acute kidney injury in these patients remains unchanged. Creatinine, the most common renal dysfunction biomarker in use, has many disadvantages, such as tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 77 publications
0
37
0
4
Order By: Relevance
“…Should a single biomarker or a combination of several be used? 24 A major issue concerning AKI criteria is their relevance to the perioperative period. Many surgical patients arrive in hospital without preoperative sCr concentrations.…”
Section: Definition Of Acute Kidney Injurymentioning
confidence: 99%
“…Should a single biomarker or a combination of several be used? 24 A major issue concerning AKI criteria is their relevance to the perioperative period. Many surgical patients arrive in hospital without preoperative sCr concentrations.…”
Section: Definition Of Acute Kidney Injurymentioning
confidence: 99%
“…Liver-type fatty acid-binding protein (L-FABP) has been considered as an important cellular antioxidant during oxidative stress by maintaining low levels of free fatty acids in the cytoplasm of tubular cells through facilitation of intracellular metabolism and excretion in urine. In a number of studies, urine L-FABP has been able to reliably predict the occurrence of AKI and death in ICU patients [64]. Recently, Costa et al found that erythrocyte superoxide dismutase (SOD1) activity could play a role as an early marker of septic AKI and could be seen as a new research avenue in the field of biomarker in AKI [67].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Novel biomarkers for acute renal failure are on the horizon. 4 Nevertheless, the variability in the clinical outcome makes it difficult to predict the risk for an individual patient. Former research suggests that genetic diversity contributes to CSA-AKI.…”
Section: Introductionmentioning
confidence: 99%